The Canadian Open Neuroscience Platform-An open science framework for the neuroscience community. - Rachel J Harding; Patrick Bermudez; Alexander Bernier; Michael Beauvais; Pierre Bellec; Sean Hill; Agâh Karakuzu; Bartha M Knoppers; Paul Pavlidis; Jean-Baptiste Poline; Jane Roskams; Nikola Stikov; et al. (PLoS Computational Biology)
The Canadian Open Neuroscience Platform (CONP) takes a multifaceted approach to enabling open neuroscience, aiming to make research, data, and tools accessible to everyone, with the ultimate objective of accelerating discovery. Its core infrastructure is the CONP Portal, a repository with a decentralized design, where datasets and analysis tools across disparate platforms can be browsed, searched, accessed, and shared in accordance with FAIR principles. Another key piece of CONP infrastructure is NeuroLibre, a preprint server capable of creating and hosting executable and fully reproducible scientific publications that embed text, figures, and code. As part of its holistic approach, the CONP has also constructed frameworks and guidance for ethics and data governance, provided support and developed resources to help train the next generation of neuroscientists, and has fostered and grown an engaged community through outreach and communications. In this manuscript, we provide a high-level overview of this multipronged platform and its vision of lowering the barriers to the practice of open neuroscience and yielding the associated benefits for both individual researchers and the wider community.